The Effectiveness of Roblox Gamified Learning for Junior High School EFL Students - Maryuli Setyoko; Juita Triana; Abdul Ngafif (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This literature study tested the effectiveness of gamification through the Spelling Race game on Roblox in improving the motivation, engagement, and English learning outcomes of junior high school students. The study used a pre-experimental design with a single-group pretest and posttest with 23 students selected purposively. The findings showed improved learning achievement. The average score increased from 74.17 in the pretest to 79.65 in the posttest, a total score increase of 5.48 points. A paired-sample t-test confirmed a significant difference, with t = 4.78 exceeding the critical t = 2.074. Gamification features in the Roblox app, such as achievements, leaderboards, and visualized feedback, increased student motivation and participation. Students were more actively engaged during the learning process. Interactive activities in the game supported vocabulary, pronunciation, and spelling development. This implementation faced challenges. Schools faced limited technological resources. Teachers needed clear teaching strategies, and learning activities needed to be aligned with the curriculum. Gamification through Roblox showed strong potential as an effective approach to improving English learning outcomes.